Analisis Dekonstruksi Tokoh Itachi, Sasuke, dan Obito Uchiha dalam Anime Naruto Shippuden: Perspektif Jacques Derrida - Hisyam, Hisyam (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to analyze the characters Itachi Uchiha, Sasuke Uchiha, and Obito Uchiha in the anime Naruto Shippuden by Masashi Kishimoto using Jacques Derrida's deconstruction approach. This anime is highly popular and has created many phenomena in the global community. Its characters have a significant influence on the audience, both in terms of lifestyle and attitude. In this research, the three main characters are analyzed based on the themes of binary opposition, logical inconsistency, and new construction. Itachi Uchiha is examined in terms of his sacrifice and betrayal, Sasuke Uchiha in terms of his quest for revenge and truth, and Obito Uchiha in terms of character transformation and redemption. The research method used is descriptive qualitative with an in-depth analysis of important scenes from the anime. The results of the study show that these characters are complex and have many layers that can be interpreted differently depending on the perspective used.